Nutrient composition and physico-chemical characteristics of Loquat (Eriobotrya japonica) seed oil - Ladan Rashidi; Zohreh Golmohamadi (Islamic Azad University, 2018)
Useful medicinal and chemical properties of different parts of Eriobotrya Japonica seeds including flowers, fruits, and leaves have been investigated. In this study, fat content, moisture, unsaponifiable matter, saponification and iodine values, free fatty acid compound, individual sterols, antioxidant activity, total phenol, tannin, and flavonoids content, and detection and quantification of polyphenol compounds of the extracted oil of Loquat seeds were determined. Extracted oil percentage of the seeds was obtained 0.79-1.51 (w/w%) using soxhlet extractor. Moisture of extracting oil was obtained (0.03±0.01) (w/w%). Iodine and saponification values of Loquat seed oil were obtained 92.64±0.18 (mg KOH/g fat) and 196.3±0.2 (mg I2/g fat), respectively. Unsaponifiable matter was too high about 21.44±0.02%. The amount of unsaponifiable matter shows that this oil is rich in tocopherols, sterols and squalene. Predominant fatty acids in Loquat seed oil were oleic acid (C18:1cis) (33.30±0.03%) followed by linoleic acid (C18:2cis) (31.00±0.20%) then palmitic acid (C16:0) (17.50±0.05%). The most abundant sterol of Loquat seed oil was β-Sitosterol (88.61±0.50%). The most content of triglycerides related to ECN48 (71.4±0.40%). In addition, results showed that unsaturated fatty acid content (FAC) in sn-2-position was higher than that of sn-1,3-positions. The antioxidant activity percentage of Loquat seed oil was 94.33±0.05%. Total phenol, tannin, and flavonoid content of Loquat seed oil extract were obtained 30.38±0.60 (mg GAE/g dry matter), 0.493±0.01 (mg GAE/g dry matter) and 6.97±0.10 (mg QE/g dry matter), respectively. In addition, ferulic acid was known the main polyphenol compound in Loquat seed oil extract. Loquat seed oil can be used in the food industry, cosmetics, paint, and soaps.